2017
DOI: 10.3390/ijerph14091085
|View full text |Cite
|
Sign up to set email alerts
|

Association between Emotional Symptoms and Job Demands in an Asian Electronics Factory

Abstract: Various work-related issues including mental health have been described for the electronic industry. Although East Asian countries play important roles in the electronics industry, the association between job demands and emotional symptoms has been rarely examined. The present study recruited 603 workers from either office or clean room environments in an electronics factory in Taiwan. Their personal factors, work-related factors, and emotional symptoms were assessed by a self-administered questionnaire. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It has been shown that job demands were positively related to employees' trait anxiety (Richardsen et al, 1992 ) or work anxiety (Maria et al, 2018 ). Emotional job demands were also found to be significantly related to employees' depressive symptoms and emotional exhaustion (Huang et al, 2017 ; Thuynsma and De Beer, 2017 ; Maria et al, 2018 ). In the context of schooling, Yin et al ( 2016 ) also reported that the emotional job demands of teaching were positively related to teachers' emotional exhaustion and negatively related to teaching satisfaction.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…It has been shown that job demands were positively related to employees' trait anxiety (Richardsen et al, 1992 ) or work anxiety (Maria et al, 2018 ). Emotional job demands were also found to be significantly related to employees' depressive symptoms and emotional exhaustion (Huang et al, 2017 ; Thuynsma and De Beer, 2017 ; Maria et al, 2018 ). In the context of schooling, Yin et al ( 2016 ) also reported that the emotional job demands of teaching were positively related to teachers' emotional exhaustion and negatively related to teaching satisfaction.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Over 800,000 employers belonged to the industry in Taiwan in 2016 [ 2 ]. In addition to chemical and physical hazards, the work environment of the industry may contain ergonomic hazards, such as repetition, lifting, and awkward posture [ 3 6 ], making the population vulnerable to developing musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the electronics industry is known for its rapid technological innovation, global competition, operation on shift work, and performance-based pay systems [ 3 , 15 ]. The association between psychological stress and psychological problems in the industry has been identified [ 6 ], but very few studies have investigated the psychosocial risk factors for shoulder disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the electronics industry is known for its rapid technological innovation, global competition, operating on shift work, and performance-based pay systems [3,15]. The association between psychological stress and psychological problems in the industry has been identi ed [6], but very few studies investigated the psychosocial risk factors for shoulder disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Over 800,000 employers belong to the industry in Taiwan in 2016 [2]. Besides chemical and physical hazards, the work environment of the industry may contain ergonomic hazards, such as repetition, lifting, and awkward posture [3][4][5][6], making the population vulnerable to develop musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%